Research summary, possible mechanisms and perspectives of gut microbiota changes causing precocious puberty - Bao, Maorong; Wu, Rui; Li, Jingwei; Tang, Runan; Song, Cui (Frontiers in Nutrition, 2025)
The increasing global incidence of precocious puberty, linked to environmental, metabolic, and genetic factors, necessitates innovative therapies beyond gonadotropin-releasing hormone (GnRH) analogs. Accumulating evidence implicates gut microbiota dysbiosis as a pivotal regulator of pubertal timing via interactions with hormone metabolism (e.g., estrogen reactivation via β-glucuronidase), neuroendocrine pathways (nitric oxide signaling), and immune-inflammatory responses. This review delineates taxonomic alterations in central precocious puberty (CPP) and obesity-related subtypes, including Streptococcus enrichment and Alistipes depletion, alongside functional shifts in microbial metabolite production. Mechanistic insights highlight microbiota-driven modulation of the hypothalamic–pituitary-gonadal (HPG) axis, leptin/insulin dynamics, and epigenetic regulation. Emerging interventions-probiotics, fecal microbiota transplantation (FMT), and dietary modifications-demonstrate efficacy in preclinical models and early clinical studies for delaying puberty onset and restoring hormonal balance. Translational efforts to validate these strategies are critical for addressing the clinical and psychosocial challenges posed by precocious puberty, positioning gut microbiota modulation as a novel therapeutic frontier in pediatric endocrinology.